Control of wpt transmitter coils for power distribution to two receiver coils without feedback - Heo, Jun; Park, Sungyeal; Kim, Sang Won; Cho, In Kui; Hong, Songnam; Park, Yong Bae (Energies, 2021)
This paper proposes the algorithm to control the current ratio of the transmitting (Tx) coils for proper power distribution to the two receiving (Rx) coils in wireless power transfer (WPT) system. The proposed algorithm assumes that each Rx coil appears at different times to consider the situation where multiple users request power transmission as practically as possible. That is, suppose the second Rx coil enters the charging space later than the first Rx coil. When each coil enters the charging space, only the Tx coil is used to obtain the value required for calculation. Using the obtained result, the optimized Tx coil current is calculated by the proposed algorithm and proper power distribution to both Rx coils is achieved. Three Tx coils and two Rx coils are constructed using the ANSYS MAXWELL simulation tool. As a result of applying the proposed algorithm, it was confirmed that a similar level of power was transmitted between 40∼60%, respectively. The sum of the power transmitted to the two Rx coils also appeared as more than 75%.
Keywords: Current ratios; Max-min problem; Max/min; Optimisations; Power; Power distributions; Power transfer systems; Receiver coil; Transmitter coils; Wireless power; Magnetic resonance; Max-min problem; Optimization; Power distribution; Wireless power transfer